Evaluación del nivel de satisfacción de los servicios brindados a usuarios externos del Gobierno Autónomo Descentralizado del Cantón Bolívar - Candela Zambrano, Gema Haydee (2018)
With the implementation of the evaluation instrument to external users was to determine the level of satisfaction of services provided by the decentralized autonomous Government of the Bolívar canton placing it 3.07 quantitative and qualitative way as a regular. To achieve this goal, activities were carried out as: identification of the services offered by the institution, evaluation of the services provided, so a survey was applied where it is established how dissatisfied 37,33% of external users. In addition developed a causal analysis of the problems affecting the satisfaction of users to rank them by means of techniques such as diagram Paretto and cause and effect diagram, which determined the subcausas affecting the satisfaction. Therefore, to improve the services offered by the decentralized autonomous Government of the Bolívar canton, was designed a proposal for corrective actions, focused on three fundamental aspects which are: formation of a Commission of oversight of social control for monitoring of planning works use of assertive communication in the funcionario-usuario relationship, and the implementation of a system for monitoring and evaluation of the level of satisfaction external users. Thus it is established that the design of a proposed improvement to the services provided by the decentralized autonomous Government of the Bolívar canton, it is essential to increase the efficiency, effectiveness, affectivity and quality of services and mitigate the shortcomings that may occur, it also allows to raise the level of satisfaction of the external users.